Dolphin tale [videorecording (DVD)] - Smith, Charles Martin; Judd, Ashley; Freeman, Morgan; Connick, Harry. Jr., 1967-; Kristofferson, Kris; Sternhagen, Frances, 1930- (Warner Home Video, 2012)
Inspired by the amazing true story of a brave dolphin and the compassionate strangers who banded together to save her life. Swimming free, a young dolphin is caught in a crab trap, severely damaging her tail. She is rescued and transported to the Clearwater Marine Hospital, where she is named Winter. But her fight for survival has just begun. Without a tail, Winter's prognosis is dire.